IMPACT OF EMOTIONAL INTELLIGENCE ON THE BEHAVIOR STRATEGIES IN CONFLICTS - Bondarchuk, Dar`ia; Proskurka, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The purpose of the study is to study the influence of emotional intelligence of young people on the choice of strategy of behavior in conflict. The relevance of the research is determined by the present, the socio-political situation both in Ukraine and the whole world. The following methods of psychodiagnostic research were applied: N. Hall's method of diagnosing emotional intelligence; the Thomas-Kilman questionnaire "Determining the type of personality behavior in a conflict situation", the "Self-assessment of conflict" test by V. Ryakhovsky and the social self-control test by M. Snyder (adapted by A. Rukavishnikov and M. Sokolova). The results. During the empirical study, it was established that almost half of the respondents had a low level of emotional intelligence. Examining the components of emotional intelligence, it was determined that achievers have problems with managing their emotions and self-motivation, while emotional awareness and empathy are best developed. At the same time, it was established that according to the results of the Thomas-Kilman questionnaire "Determining the type of personality behavior in a conflict situation", the majority of respondents use avoidance and compromise strategies. Based on the results of V. Ryakhovsky's "Self-Assessment of Conflict" method, it was determined that the majority of respondents (60.0%) have weakly expressed conflict. At the same time, a quarter (25.0%) of respondents revealed pronounced or highly pronounced conflict. It was also determined that according to the results of the test of social self-control by M. Snyder (adapted by A. Rukavishnikov and M. Sokolova), the greater half (56.6%) of the respondents have an average level of social self-control. Conclusions. According to the results of statistical data processing, it was determined the existence of a positive correlation between the level of emotional intelligence and the strategy of behavior in the conflict "cooperation" (р ≤ 0.01), the strategy "compromise" (р ≤ 0.05) and a negative correlation associated with the "avoidance" style (р ≤ 0.01). It was also revealed the existence of positive correlations between such components of emotional intelligence as "self-motivation" and "managing one's emotions" with the conflict behavior strategy "cooperation" (p ≤ 0.05), "emotional awareness" and "recognizing the emotions of others people" with the "compromise" strategy (p ≤ 0.05), "emotional awareness" with the "cooperation" strategy and "empathy" with the "compromise" strategy (p ≤ 0.01). Negative correlations were found between "emotional awareness", "managing one's own emotions" and the strategy of "avoidance" (p ≤ 0.01), between "recognition of other people's emotions" and the strategy of "competition" (p ≤0.01), between empathy on "rivalry" (p ≤ 0.01). Thus, a conclusion was made about the influence of emotional intelligence on the choice of a behavior strategy in a conflict among young people